Perubahan Pola Perilaku Sosial Masyarakat Kampung Adat Kuta terhadap Era Modernisasi - Riswandi Nurrohman; Fina Alyani Imanda Putri; Wulan Nur Sabilla Putri; Ammar Muzakki; Rahmat Sholeh; Yani Sri Astuti (Universitas 45 Surabaya, 2024)
Kampung Kuta is one of the traditional villages in West Java located in Ciamis Regency. The people in Kampung Kuta have a unique culture and become a reference for the survival of all elements of society there. However, on the other hand, the phenomenon of modernization has spread throughout the world and affected the lives of people including the people of Kampung Kuta. This qualitative research using observation and interview methods succeeded in finding important information about the attitude of the people of Kampung Kuna towards modernization. This modernization is not rejected by the people of Kuta Village as long as it does not violate the customary rules that are believed, therefore adaptation during the era of modernization in Kuta Village is an interesting thing to study because new things that come from modernization can adapt and go hand in hand with the customs that are believed.